Enhancing Self Efficacy Of Prolanis Group On Self Assesment Of Diabetic Foot Early Detection Based On Health Belief Model Theory And Bandura’s Self Efficacy - Atmojo, Didik Susetiyanto; Kristanto, Heny; Irawan, Hengky (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Diabetes Mellitus (DM) complications are serious problems for patients and their families. . The purpose of this study was to improve Self Efficacy on the ability to detect the risk of diabetic foot injury.The research design used was pre-experimental research with a one group pre-post test design approach. Respondents of this study were the Clinic Prolanis Group dr. Chreslina Subagyo, Kediri City Collecting data with clinical questionnaire sheet self-efficacy skills in order to determine the increase in self-efficacy. Based on the Wilcoxon test above, the p value = 0.000, which means that action given caused a changed or increased in a person's self-assessment This study revealed that the potential impact of self-efficacy, outcome expectations considered in the education program for patients. Therefore, the use of self-efficacy theory when designing patient education interventions could enhance diabetes self-care